Critical Role of Flow Cytometric Immunophenotyping in the Diagnosis, Subtyping, and Staging of T-Cell/NK-Cell Non-Hodgkin’s Lymphoma in Real-World Practice: A Study of 232 Cases From a Tertiary Cancer Center in India - Tembhare, Prashant R.; Chatterjee, Gaurav; Chaturvedi, Anumeha; Dasgupta, Niharika; Khanka, Twinkle; Verma, Shefali; Ghogale, Sitaram G.; Deshpande, Nilesh; Girase, Karishma; Sengar, Manju; Bagal, Bhausaheb; Jain, Hasmukh; et al. (Frontiers in Oncology, 2022)
Background: T-cell/NK cell non-Hodgkin lymphoma(T/NK-NHL) is an uncommon heterogeneous group of diseases. Current classification of T/NK-NHL is mainly based on histopathology and immunohistochemistry. In practice, however, lack of unique histopathological patterns, overlapping cytomorphology, immunophenotypic complexity, inadequate panels, and diverse clinical presentations pose a great challenge. Flow cytometric immunophenotyping (FCI) is a gold standard for the diagnosis, subtyping, and monitoring in many hematological neoplasms. However, studies emphasizing the role of FCI in the diagnosis and staging of T/NK cell NHL in real-world practice are scarce. Methods: We included T-NHL patients evaluated for the diagnosis and/or staging T/NK-NHL using FCI between 2014 to 2020. We studied the utility of FCI in the diagnosis and subtyping of T/NK-NHL and correlated the FCI findings with the results of histopathological/immunohistochemistry. For the correlation purpose, patients were categorized under definitive diagnosis and subtyping, inadequate subtyping, inadequate diagnosis and misdiagnosis based on the findings of each technique. Results: A total of 232 patients were diagnosed with T/NK-NHL. FCI findings provided definitive diagnosis in 198 patients and subtyping in 187/198(95.45%) patients. Correlation between FCI and histopathological/immunohistochemistry results (n=150) demonstrated an agreement on the diagnosis and subtyping in 69/150(46%) patients. Of remaining cases, the diagnosis and subtyping was inadequate in 64/150(42.7%), and 14/150(9.33%) were misdiagnosed on histopathology/immunohistochemistry results. FCI provided definitive diagnosis and subtyping in 51/64 (79.7%) patients. Among these, 13 patients diagnosed as peripheral T-cell lymphoma not-otherwise-specified were reclassified (Angioimmunoblastic T-cell lymphoma (AITL)-11 and Prolymphocytic leukemia-2) on FCI. It corrected the diagnosis in 14 patients that were misdiagnosed (6- B-NHL, 3-Hodgkin lymphoma, 1-Acute Leukemia and 1-Subcutaneous panniculitis-like T-cell lymphoma) and misclassified (3- T-NHL) on histopathological results. AITL was the commonest T-NHL misclassified on histopathological results. FCI also confirmed the definite involvement in 7/83(8.4%) and 27/83(32.5%) bone marrow samples reported as suspicious and uninvolved respectively on histopathological evaluation. Conclusion: AITL was the most frequently diagnosed T/NK NHL in this study. FCI provided a distinct advantage in detecting BM involvement by T/NK-NHL, especially in patients with low-level involvement. Overall, our study concluded that FCI plays a critical role in the diagnosis, subtyping and staging of T/NK NHL in real-world practice.